Nata production from mango processing by products - Endencia, Julia Mercy E. (1990)
ABSTRACT Nata, a by-product of a respiratory type of metabolism by the organism Acetobacter aceti sub. xylinum was developed using mango processing by-products, specifically, expired canned mango juice as its main growth medium. In Phase I, growth cultures were prepared using 1--11°Bx, 15-16°Bx, 20-21°Bx and 24°Bx sugar concentrations at 100% 1:1 (v/v) and 1:0.5 (v/v) mango juice to water dilution ratios. Objective evaluation revealed that the most acceptable nata was produced using 1:0.5 (v/v) mango juice to water ratio and 24°Bx sugar concentration. The effect of wide and narrow temperature ranges of 25-32°C (room temperature) and 28-31°C (controlled temperature), respectively plus the use of the two nitrogen sources, NH₄H₂PO₄ and (NH₄)₂SO₄ on the nata formed were evaluated in Phase II. Objective and sensory evaluation resulted to the selection NH₄H₂PO₄ as the nitrogen and 28-31°C as the growth culture's temperature range. Utilizing the established conditions from Phase I and II, a laboratory scale production of nata de mangga was performed to determine the cost of production and critical control points involved in Phase III. The cost of production incurred to produce nata de mangga in syrup was P 21.30 per fancy oval jar with a drained weight of 320 grams.